KIT polymorphisms and mutations determine responses of neoplastic mast cells to bafetinib (INNO-406) - Peter, Barbara; Hadzijusufovic, Emir; Blatt, Katharina; Gleixner, Karoline V.; Pickl, Winfried F.; Thaiwong, Tuddow; Yuzbasiyan-Gurkan, Vilma; Willmann, Michael; Valent, Peter (Experimental hematology, 2010)
Advanced systemic mastocytosis (SM) is characterized by uncontrolled growth of neoplastic mast cells (MC) and drug resistance. The tyrosine kinase receptor KIT is often mutated and activated and thus contributes to malignant growth of MC. Therefore, KIT-targeting drugs are currently tested for their ability to block growth of malignant MC. We determined the effects of the multikinase inhibitor INNO-406 (bafetinib) on primary neoplastic MC, the canine mastocytoma cell line C2, the human MC leukemia cell line HMC-1.1 bearing the KIT mutant V560G, and HMC-1.2 cells harboring KIT V560G and KIT D816V. INNO-406 was found to inhibit proliferation in HMC-1.1 cells (IC 50: 30−40 nM), but not in HMC-1.2 cells or primary neoplastic cells in patients with KIT D816V-positive SM. In canines, growth-inhibitory effects of INNO-406 were seen in C2 cells (IC 50: 50−100 nM) exhibiting a KIT exon 11 internal tandem-duplication and in primary neoplastic MC harboring wild-type exon 11, whereas no effects were seen in MC exhibiting a polymorphism at amino acid 581 in exon 11. INNO-406 was found to block KIT phosphorylation and expression in HMC-1.1 cells and C2 cells, but not in HMC-1.2 cells, whereas Lyn-phosphorylation was blocked by INNO-406 in all types of MC. In neoplastic MC, the major target of INNO-406 appears to be KIT. Drug responses may depend on the presence and type of KIT mutation. In human MC, the KIT D816V mutant introduces resistance, and in canine mastocytomas, an exon 11 polymorphism may be indicative of resistance against INNO-406.